Защита прав меньшинств - United Nations for Human Rights Office of the High Commissioner (United Nations, 2024)
This Guide sets out in detail the content of comprehensive anti-discrimination law. It provides legislators and advocates with the tools to develop anti-discrimination legislation consistent with international legal standards on the rights to equality and non-discrimination. It aims to assist States in meeting their core international law obligations to respect, protect, and fulfil the rights to equality and non-discrimination. This Guide also includes practical examples to assist law- and policy-makers. It also provides specific guidance on the link between anti-discrimination law on the one hand, and minority rights on the other.